SOME NOTES OF THE HYDROGRAPHIC SURVEYS IN INDONESIAN WATERS - Pardjaman, Djamhir (Marine Research in Indonesia, 1977)
During the period of 1969 to 1975 "JANHIDROS" carried out several hydrographic surveys and marine investigations in the Sunda Shelf and its adjacent waters. Data obtained during these surveys has shown that the general characteristics of the area which are primarily governed by the monsoonal regime are also affected by local conditions. The purpose of this paper is to render data based on these surveys which may be useful to complement environmental information.